Ventures Within Fisheries Value Chain that Men and Women Participate in Nairobi City County, Kenya - Kizito, Paul; Kimani, Elishiba; Lodiaga, Mildred (Advances in Social Sciences Research Journal, 2017)
The government of Kenya has put in place an integrated package of service to reduce gender disparities through credit facilitation, which includes business skills, enhanced and increased access to the viable markets among others. It is in this respect that this study sought to establish the status of men and women in the entrepreneurial fisheries activities in Kenya; with an objective to establish various ventures within fisheries value chain that men and women participate. The social structural theory developed by Connell (1987) based on patriarchal system and social mechanisms in place to reinforce and sustain the ideology. The theory provides a substantive justification of women’s subordination in the fisheries value chain. The study findings showed that men were prominent in economically high end City market and South C market while women were more in the marginal Kariobangi market. The findings revealed that men had controlled the high-end value chains namely; aquaculture/fish harvesting, transportation, distribution, middle trade, and large scale while women were more focused on the lower end value chain namely; grading/sorting/gleaning and market sellers.